Status pemberian ASI terhadap status gizi bayi usia 6-12 bulan - Normayanti Normayanti; Nila Susanti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2013)
Background: Coverage of exclusive breastfeeding in Indonesia fluctuate and showed a declining trend over the last three years. Coverage of exclusive breastfeeding of Palangka Raya city is still very low at around 23.30%. There are several variables suspected as the cause of the malnutrition problem, the variables are status of breastfeeding, mother's education level, mother's employment, mother’s knowledge of nutrition and counseling status of breastfeeding.Objective: This study aimed to determine the effect of breastfeeding status on the nutritional status of infants aged 6-12 months in the working area of UPTD Puskesmas Kalampangan Palangka Raya city.Method: The study design used was a case-control with 1:2 ratio, the case are infants aged 6-12 months with low nutritional status, whereas the comparison are infants aged 6-12 months with normal nutritional status. The dependent variable is the nutritional status and the independent variables are breastfeeding status, mother's education level, mother's employment, mother’s knowledge of nutrition, and breastfeeding counseling status. Data analysis was performed by univariate, bivariate (Chi-Square) and multivariate (logistic regression). Results: From the 5 (five) variables were analyzed, 2 (two) variables independently became risk factor for malnutrition are status of breastfeeding (OR=6.667) and the counseling status of breastfeeding (OR=3.215). But together (simultaneously), only breastfeeding status has an influence on the nutritional status of infants, and non-exclusive breastfeeding was significant as a risk factor for malnutrition (OR=5.126). Probability infant to experience malnutrition due to breastfeeding status no exclusive is at 25.54%. Conclusion: Breastfeeding status has an influence on the nutritional status of infants and non-exclusive breastfeeding was significant as a risk factor for malnutrition among infants aged 6-12 months.